Peran Manajemen Sumber Daya Manusia (SDM) Terhadap Kinerja Pegawai Perbankan Syariah - Filzah Aulia; Siti Jamilah (CV. ULIL ALBAB CORP, 2024)
This article explores the role of human resource management (HR) on the performance and quality of sharia banking employees. Using a literature review method or literature study with a qualitative descriptive approach, this article explains the importance of HR management in sharia banking operations. It was found that the lack of human resources who are experts in sharia finance is one of the main obstacles. The importance of education and training, appropriate recruitment, career development, Islamic organizational culture, collaboration with educational institutions, as well as empowerment and appreciation are identified as efforts that can be made to improve the quality of human resources. In addition, clear competency standards and certification are also considered important. In conclusion, effective HR management can improve employee competency and quality, which in turn will support the performance and progress of sharia banking.